2013
DOI: 10.1111/jgh.12134
|View full text |Cite
|
Sign up to set email alerts
|

Controlled attenuation parameter for non‐invasive assessment of hepatic steatosis: Does etiology affect performance?

Abstract: CAP is a novel, non-invasive tool that can detect and quantify steatosis accurately among CHBV, CHCV, and NAFLD patients, the accuracy being similar for all the three groups of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
83
1
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(91 citation statements)
references
References 30 publications
(71 reference statements)
4
83
1
3
Order By: Relevance
“…with areas under the ROC curves of 0.84, 0.86 and 0.93 for >10 % (S1), >33 % (S2) and >67 % (S3) steatosis respectively [88] or with areas under the ROC curves of 0.79, 0.76 and 0.70 for >5 %, >33 % and >67 % steatosis respectively [89]. There is evidence that the aetiology of steatosis does not affect the accuracy of CAP™ [90]. …”
Section: Ultrasound Modalitiesmentioning
confidence: 99%
“…with areas under the ROC curves of 0.84, 0.86 and 0.93 for >10 % (S1), >33 % (S2) and >67 % (S3) steatosis respectively [88] or with areas under the ROC curves of 0.79, 0.76 and 0.70 for >5 %, >33 % and >67 % steatosis respectively [89]. There is evidence that the aetiology of steatosis does not affect the accuracy of CAP™ [90]. …”
Section: Ultrasound Modalitiesmentioning
confidence: 99%
“…A measurement method is precise if it gives values that are both accurate and reproducible. Several studies have investigated the diagnostic accuracy of CAP in the quantification of liver steatosis by comparing the results to liver histology [4,[6][7][8][9][10][11]. Data on the reproducibility of CAP measurements are few.…”
Section: Introductionmentioning
confidence: 98%
“…Some recent studies have shown that CAP significantly correlates with the grade of steatosis in patients with CLD of different etiologies [22][23][24] . However, the accuracy of CAP for quantifying steatosis in patients with CLD varies among studies.…”
Section: Introductionmentioning
confidence: 99%